Heterologous 5' flanking regions do not support in vitro template activity of a Drosophila melanogaster tRNA(Val3b) gene. - Mackay, R M (1988)
The 5' and 3' structure of a Drosophila tRNA(Val3b) gene was investigated to examine the defect which caused the extremely low in vitro transcription template activity of the gene. Recombinant genes were constructed linking 5' and 3' flanking regions from tRNA genes which were active in vitro templates (tRNA(Val4), tRNA(Arg), tRNA(Ser7)) to the tRNA(Val3b) gene. None of the recombinant genes were effective in vitro templates. The defect in tRNA(Val3b) was demonstrated to reside in the 5' flanking region of the gene and deletion analysis indicated that no specific transcription inhibitor sequence was present 5' to the gene. The data suggest that the effect of 5' flanking sequences on in vitro transcription of the tRNA(Val3b) gene requires a specific relationship between the tRNA gene and the flanking sequence.